Philosophy of exhibition Аstana ЭКСПО- 2017 is a project «Energy of the future» (Journal of Philosophy Culture and Political Science, 2015)
In article it is noted that in successful realization of modernizationmost important tasks necessary for our country so-called breakthroughprojects which main feature is that they cover areas of the most differentphenomena of culture can play a big role. To such projects, accordingto the author of article, it is possible to carry the exhibition opening in2017 in Kazakhstan ASTANA EXPO-2017. It is claimed that it is possibleto call the Energy of the Future project declared as the main subject ofthe forthcoming exhibition philosophy ASTANA EXPO-2017 as this largescalecomprehensive project demands, respectively, the deepest, broad,integrated approach to the world and the person in it, that is philosophicalapproach.
Keywords: «energy of the future»; «green economy»; ecological outlook; power ecological development; power ecological strategy; energy efficiency; power technologies; steady ecodevelopment.